A mobilidade territorial dos trabalhadores da construção civil na produção da verticalização no bairro Aldeota em Fortaleza - Mendes, Mariana Fernandes (2008)
Since 70’s in 20th century, an astonishing occupation of Aldeota’s neighborhood made a new centrality in the urban scene of Fortaleza. From this period onward, Aldeota has being transformed by capital property processes which appropriated the forms of use and occupation of space by verticalization. The proliferation of buildings has been predominant for increasing of shops and high standard condominiums. Then Aldeota became a magnet for the working class, especially for construction workers, as soon as necessary for the recruitment of these workers to construct more buildings which are part of the verticalization process that signals a modern metropolis symbols. These workers are going to Aldeota every day and returns to the most varied neighborhoods in Fortaleza where they lives, showing to us the labour mobility. The distance between the home and the job of these workers is the way that the Capitalism uses to get the worker’s power’s job to itself by the consumption. And also, this working class needs better conditions of housing and work, specially because it’s a risk job and much physical effort to do it. This monopolist industry works through a large corporation that covers the three sectors: industrial, commercial and is a service. Meanwhile, the industrial sector adds more labour-worker, however, the saturate space in Aldeota became a paradigm for the construction of new buildings, showing a new paradigm. The construction work which has acting in the neighborhood has decreased the number of buildings as soon as occurs the space became saturated in the area, given that, another districts has coming more attractive to the momentum building for more enjoyable space, such as Varjota and Meireles. The fact is: even if there is a tendency to decrease construction works in Aldeota, the number of workers in construction grows up as the city continues to grow in other directions. And also do not extinguish some approaches, especially sociological, which want to believe in a possible end of the work. So the Aldeota’s civil constructing is passing for a stagnant while workers are under "construction". The building and improvements fights are what are they build.